Do HIV provider and client perspectives align on person-centered care? Lessons learned from implementation of the Person-Centered Care Assessment Tool (PCC-AT) in HIV treatment settings in Ghana. - Jessica E Posner; Malia Duffy; Caitlin Madevu-Matson; Henry Tagoe; Amy Casella; Melissa Sharer; Henry Nagai (Public Library of Science (PLoS), 2024)
Person-centered care (PCC) is foundational to improve client's experiences in care while advancing HIV-related outcomes. However, information is scarce on how to assess PCC in HIV treatment settings. This study team developed the PCC assessment tool (PCC-AT) to assess the performance in HIV clinics in Ghana. The objectives of this study were to: (1) pilot the PCC-AT and assess scoring consistency and reliability among clients and providers; and (2) assess content validity of the PCC-AT through client key informant perspectives and experiences. An analysis of similarities and differences in PCC-AT domain scores between ART providers and clients was conducted to assess score reliability. Axial and open coding of transcripts using NVivo identified key themes. Findings indicate that the PCC framework aligns with client's priorities, additionally two out of the three PCC domain scores demonstrated consistency between ART providers and clients. Emerging differences in ART provider and client perspectives highlighted opportunities for growth and underscored the importance of continually gathering client feedback as an integral component of a PCC assessment to continually strengthen ART services.